Современные проблемы изучения комплексных объектов и базисные стратегии методологии научного исследования - Буряк, В.В.; Махин, С.А.; Шостка, В.И. (Культура народов Причерноморья, 2014)
В работе анализируются различные аспекты междисциплинарного подхода в ходе изучения
комплексных объектов. Актуальность темы исследования обоснована тенденцией реформирования
образования в связи с появлением новых отраслей научного знания и специальных дисциплин. Интеграция
методологических усилий необходима, поскольку в процессе исследования сложных объектов возникает
потребность оценки эвристического потенциала эпистемологического инструментария для
компетентностного изучения объектов и систем. Рассмотрены различные когнитивные стратегии
междисциплинарного подхода. Интегрированный когнитивный подход к изучению методологии
является важным, поскольку в случае исследования комплексных объектов целесообразно проводить
анализ при помощи эпистемологического инструментария, когда необходимо применение нескольких
взаимодополняющих познавательных ресурсов. У роботі аналізуються різні аспекти міждисциплінарного підходу в ході вивчення
комплексних об'єктів. Актуальність теми дослідження обгрунтована тенденцією реформування освіти
у зв'язку з появою нових галузей наукового знання і спеціальних дисциплін. Інтеграція методологічних
зусиль необхідна, оскільки в процесі дослідження складних об'єктів виникає потреба оцінки
евристичного потенціалу епістемологічного інструментарію для компетентнісного вивчення об'єктів і
систем. Розглянуто різні когнітивні стратегії міждисциплінарного підходу. Інтегрований когнітивний
підхід до вивчення методології є важливим, оскільки у разі дослідження комплексних об'єктів доцільно
проводити аналіз за допомогою епістемологічного інструментарію, коли є необхідним застосування
декількох взаємодоповнюючих пізнавальних ресурсів. The paper discusses different methodological strategies of interdisciplinary approach in studying
complex objects. This topic seems relevant to the current trends of education reform in the light of newly
emerging specializations and special disciplines. Integration of methodological efforts is of importance because
there is a need to assess the heuristic potential of epistemological tools used in competency analysis of objects
and systems. For example, in recent years in ecology there is increasingly used the method of mathematical
modeling with clearly defined boundaries, complementing experimental techniques and methods of observation.
Any complex system is composed of parts, components, among which there are more or less strong bonds. The
availability of data on the status of one portion or element of the system assumes the availability of information
on the state of the other parts or elements, interconnected system. There is a need to develop a methodology for
fuzzy modeling and specification of the system approach in the construction of fuzzy models for complex systems
through an interdisciplinary approach. The cognitive approach is at the same time the key to solving many
problems of research which could hardly be solved previously without resorting to the analysis of cognitive
processes. Attracting specialists from different fields of knowledge to solve different problems, cognitive science
in a specific manner combines traditional basic sciences – physics, mathematics, philosophy – to help develop
new disciplines: computer science, neuroscience, biophysics, computer science, etc.